Hyperplastic Polyps and Gastroduodenal Pseudomelanosis - Akanksha Agrawal; Deepanshu Jain; Vivian Arguello; Daniel Sher (Case Reports in Gastrointestinal Medicine)
Pseudomelanosis is a rare endoscopic finding of the upper gastrointestinal tract characterized by hemosiderin deposits in histiocytes of lamina propria. We report a case of 72-year-old lady on chronic oral iron supplementation diagnosed with gastric hyperplastic polyps with background pseudomelanosis of stomach and duodenum. Concomitant occurrence of gastric pseudomelanosis, duodenal pseudomelanosis, and gastric hyperplastic polyps has never been reported. Its presence in the absence of gastritis raises question if pseudomelanosis could be associated with hyperplastic polyp. With limited literature on its etiology and prognosis, these patients should be prospectively followed and reported to study the natural history of the disease.